Global Bibliometric Analysis of Postoperative Cognitive Dysfunction (POCD) in Anesthesia: Mapping Risk Factors and Research Trends - Taupik Rahman; Anis Laela Megasari; Pramadita Elena (GLOBAL HEALTH SCIENCE GROUP, 2026)
Postoperative Cognitive Dysfunction (POCD) is a post surgical cognitive disorder and is at risk of worsening quality of life and triggering dementia. This study aimed to conduct a bibliometric analysis of scientific publications on postoperative cognitive dysfunction (POCD) published between 2014 and 2024. The analysis examined annual publication trends, the distribution of contributing countries and institutions, types of documents, publishers, and the most frequently occurring keywords, including “postoperative cognitive dysfunction,” “anesthesia,” “risk factors,” and “POCD,” based on data retrieved from the Scopus database. This study was conducted using data from the Scopus database, analysed with the help of the Publish or Perish, PRISMA flowchart, and VOS viewer tools to visually map patterns and relationships between keywords. A total of 254 articles were identified, of which 182 articles were included in the analysis. Publication trends showed a consistent increase, peaking in 2024 with 28 papers. China (53.3%) and the United States (15.3%) were the leading contributors, followed by Japan, Germany, and the United Kingdom. Most publications were original research articles (73.1%), indicating a dominance of empirical investigations. The most active journals included Frontiers in Aging Neuroscience, BMC Anesthesiology, and Neuroscience. Keyword mapping revealed five major clusters: (1) anesthesia and surgery type, (2) neuroinflammation mechanisms, (3) aging and cognitive impairment, (4) biomarkers and pharmacological interventions, and (5) postoperative care. Recent trends (2021–2024) show a shift from descriptive to mechanistic and evidence-based studies. However, research gaps persist in the areas of digital biomarkers, psychosocial factors, long-term outcomes, and younger populations. Based on data, POCD research trends have been consistently developing and showing maturity in terms of clinical and methodological approaches.